(untitled) (Revista de Ciências Agroveterinárias, 2020)
Due to the lack of consistent information regarding the application of Prohexadione Calcium to the grapevine, the objective of this work is to assess the effect of different times of application and concentrations of Prohexadione Calcium in the winegrowing performance of the Cabernet Sauvignon variety, cultivated in regions of high altitude in the State of Santa Catarina. The present study was carried out during the 2014/2015 harvest. The applications occurred at different seasons and concentrations, being subdivided in the separated inflorescence, fully bloomed, and 15 days after full flowering. Foliar area, productivity, leaf area/production ratio, branch growth, and physical-chemical parameters were assessed: pH, total acidity, soluble solids, total polyphenols, and bunch architecture. The application of Prohexadione Calcium at a dose of 250 mg L-1, carried out in the full bloom stage, increased yield of the Cabernet Sauvignon variety by 23%. This increase in productivity was related to the highest bunch mass and the highest number of berries per bunch. Prohexadione Calcium applied in the separate inflorescence phase reduced the growth of the branches. However, due to the conditions of over-vigor of the vineyard, the reduction in growth did not eliminate the need for the emergence of the branches. There was a reduction in the mass of the berry of the Cabernet Sauvignon variety with the application of Prohexadione in the concentration and times used did not influence the technological maturity (soluble solids, acidity, and Calcium, a positive characteristic in the elaboration of red wines. The application of Prohexadione Calcium pH) of the Cabernet Sauvignon grape.